Перспективність побудови методики розслідування домашнього насильства - Пчеліна, О. В.; Pchelina, O. V.; Пчеліна Оксана Василівна (Юридичний науковий електронний журнал. - 2020. - № 4. - С. 329-332, 2020)
Проаналізовано стан нормативно-правового регулювання діяльності із запобігання та протидії домашньому насильству. Наведено статистичні дані Офісу Генерального прокурора про кількість і стан кримінальних проваджень, відкритих за фактом учинення домашнього насильства впродовж 2018 – першого півріччя 2020 року. Наголошено на необхідності розробити криміналістичні рекомендації з виявлення, розкриття та розслідування такого різновиду кримінального правопорушення, як домашнє насильство, й формування відповідної окремої криміналістичної методики. Визначено завдання та принципи побудови методики розслідування домашнього насильства. Здійснено криміналістичну класифікацію домашнього насильства. Запропоновано структуру методики розслідування домашнього насильства: криміналістична класифікація та характеристика домашнього насильства; обставини, що підлягають з’ясуванню; відкриття кримінального провадження; початковий етап розслідування; наступний етап розслідування; взаємодія під час розслідування домашнього насильства; особливості тактики проведення окремих слідчих (розшукових) дій і заходів забезпечення кримінального провадження; використання можливостей судових експертиз. Водночас зазначено, що особливості відкриття кримінального провадження, початкового й наступного етапів розслідування домашнього насильства потрібно викладати у вигляді алгоритму дій з урахуванням тактичних завдань, типових слідчих версій і слідчих ситуацій.

In the article it has been noted that domestic violence is becoming more common every year, which increases both the number of domestic violence offenses and open criminal proceedings. The state of normative-legal regulation of activity on prevention and counteraction to domestic violence has been analyzed. The statistics of the Office of the Prosecutor General on the number and status of criminal proceedings opened on the fact of domestic violence during 2018 – first half of 2020 have been presented. Emphasis has been placed on the need to develop forensic recommendations for the detection, detection and investigation of such a type of criminal offense as domestic violence and the formation of a separate forensic methodology. It has been noted that the construction of methods of investigation of domestic violence is determined by both scientific and practical needs, and therefore is a promising area of forensic science in general and forensic methodology in particular, as well as activities to detect and investigate domestic violence. The tasks and principles of building a methodology for investigating domestic violence have been defined. A forensic classification of domestic violence has been made. It has been emphasized that the developed methodology of domestic violence investigation, in order to be informative and suitable for use in law enforcement activities, should fully reflect both the features of the mechanism of domestic violence and the specifics and actual state of their detection and pre-trial investigation. It has been proposed the following structure of the methodology of domestic violence investigation: forensic classification and characteristics of domestic violence; circumstances to be clarified; opening criminal proceedings; the initial stage of the investigation; the next stage of the investigation; interaction during the investigation of domestic violence; features of tactics of carrying out separate investigative (search) actions and measures of maintenance of criminal proceedings; use of opportunities of forensic examinations. It has been noted that the peculiarities of the opening of criminal proceedings, the initial and subsequent stages of the investigation of domestic violence should be covered in the form of an algorithm of actions, taking into account tactical tasks, typical investigative versions and investigative situations.

Проанализировано состояние нормативно-правового регулирования деятельности по предотвращению и противодействию домашнему насилию. Отмечено необходимость разработать криминалистические рекомендации по выявлению, раскрытию и расследованию такой разновидности уголовного правонарушения, как домашнее насилие, и формирование соответствующей отдельной криминалистической методики. Определены задачи и принципы построения методики расследования домашнего насилия. Осуществлена ​​криминалистическая классификация домашнего насилия. Предложена структура методики расследования домашнего насилия.
Prospectiveness of construction of methodology of investigation of domestic violence
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Криміналістика. Criminalistics. Криминалистика; Україна. Ukraine. Украина; домашнє насильство; domestic violence; домашнее насилие; методика розслідування домашнього насильства; method of investigating domestic violence; методика расследования домашнего насилия; криміналістична класифікація домашнього насильства; forensic classification of domestic violence; криминалистическая классификация домашнего насилия; протидія домашньому насильству; combating domestic violence; противодействие домашнему насилию